Musculoskeletal problems in diabetes mellitus - Sözen, Tümay (Eur J Rheumatol, 2018)
Diabetic patients may suffer from a wide range of musculoskeletal disorders that can cause pain and some dysfunctions in the patient and affect the treatment negatively or reduce the quality of life by causing problems in the implementation of exercise programs, which are very important in the treatment of patients with Diabetes Mellitus. Although most of these problems are also seen in non-diabetics, they are more frequently observed but are not specific to diabetics. Their physiopathology is not fully understood; there is some evidence suggesting that macro- and microvascular complications of diabetes are responsible. A diagnosis of musculoskeletal dysfunctions in diabetic patients is made by clinical findings, and there is currently no specific treatment. If the treatment of problems requires corticosteroid use, diabetes can be hard to manage. In this review, we summarized the general features, diagnosis, and treatment modalities of frequent and important musculoskeletal disorders in diabetic patients.